Software Sistem Pelaporan Akuntansi Koperasi (Silakop) Sebagai Solusi Pencatatan dan Pelaporan Keuangan Koperasi Wanita - Syaiful Hidayat, Ujang; Siwidyah Desi Lastianti; Yanna Eka Pratiwi; Indra Wijayanto; Ida (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2023)
This article discusses women's cooperatives, which have an important role in efforts to empower women and help  improve  the  welfare  of  their  members.  However,  women's  cooperatives  face  financial  reporting problems and a lack of knowledge and skills in preparing financial reports in accordance with Financial Accounting Standards for Entities Without Public Accountability (SAK-ETAP). This study aims to design and develop accounting software that can provide solutions to the problems of recording and reporting finances for women's cooperatives. This action research uses a qualitative approach, carried out in the cities of Malang  and  Surabaya  in  the  period  October-November 2022,  with  data  collected  through  interviews, observations and financial documents. The result of this research is a cooperative accounting reporting software (SiLaKop) that has been used in several KopWans in the City and Regency of Malang.